A regional benthic fauna assessment method for the Southern North Sea using Margalef diversity and reference value modelling. (June 2018) - van Loon, Willem M.G.M.; Walvoort, Dennis J.J.; van Hoey, Gert; Vina-Herbon, Christina; Blandon, Abigayil; Pesch, Roland; Schmitt, Petra; Scholle, Jörg; Heyer, Karin; Lavaleye, Marc; Phillips, Graham; Duineveld, Gerard C.A.; et al.
Highlights: A new method to assess benthic fauna conditions in the Southern North Sea region was developed. This benthic fauna assessment is based on the Margalef diversity index, reference value modelling and BENMMI software. Margelef diversity alone appeared to be the best performing index, better than multi-metric index combinations. The sensitivity and precision of Margalef diversity were demonstrated for the anthropogenic pressures fishing, organic enrichment, sedimentation and a heavy metal. This new benthic assessment is potentially suitable for implementation in other European marine regions. Abstract: The aims of this study are to develop an optimized method for regional benthic fauna assessment of the Southern North Sea which (a) is sensitive and precise (quantified as the slope and the R 2 value of the pressure-impact relationships, respectively) for the anthropogenic pressures bottom fishing and organic enrichment, (b) is suitable for estimating and modelling reference values, (c) is transparent, (d) can be efficiently applied using dedicated software; and to apply this method to benthic data from the Southern North Sea. Margalef diversity appeared to be the best performing benthic index regarding these criteria, even better than several Multi-Metric Indices (MMIs) containing e.g. AMBI (AZTI Marine Biotic Index) and ITI (Infaunal Trophic Index). Therefore, this relatively simple and very practical index, including a new reference value estimation and modelling method, and BENMMI software were selected as a common OSPAR (Oslo Paris convention) method for the benthic fauna assessment of the Southern North Sea. This method was applied to benthic fauna data from the Southern North Sea collected during the period 2010–2015. The results in general show lower normalized Margalef values in coastal areas, and higher normalized Margalef values in deeper offshore areas. The following benthic indices were compared in this study: species richness, Margalef diversity, SNA index, Shannon index, PIE index, AMBI, ITI. For each assessment area, the least disturbed benthic dataset was selected as an adjacent 6 year period with, on average, the highest Margalef diversity values. For these datasets, the reference values were primarily set as the 99th percentile values of the respective indices. This procedure results in the highest stable reference values that are not outliers. In addition, a variable percentile method was developed, in which the percentile value is adjusted to the average bottom fishing pressure (according to data from the International Council for the Exploration of the Sea, ICES) in the period 2009–2013. The adjusted percentile values were set by expert judgement, at 75th (low fishing pressure), 95th (medium fishing pressure) and 99th (high fishing pressure) percentile. The estimated reference values for Margalef diversity correlate quite well with the median depth of the assessment areas using a sigmoid model (pseudo-R 2  = 0.86). This relationship between depth and Margalef diversity was used to estimate reference values in case an assessment area had insufficient benthic data For testing the effects of bottom fishing pressure, normalized index values (NIV; index value divided by reference value) were used. The rationale for using NIVs is the assumption that, although a certain level of bottom fishing pressure will have a larger absolute effect on more biodiverse benthic communities in deeper waters than on more robust and less biodiverse coastal benthic communities, the relative effects (tested using NIVs) are comparable. A clear exponentially decreasing relationship (R 2  = 0.26–0.27, p < 0.00001) was found between both bottom surface and subsurface fishing activity (penetration depth <2 cm and >2 cm, respectively) and normalized Margalef diversity values, with an asymptotic normalized Margalef value of 0.45 at a subsurface fishing activity >2.3 sweeps/year. This asymptotic value is predominantly found in coastal waters, and probably shows that the naturally more robust coastal benthic communities have been transformed into resilient benthic communities, which rapidly recover from increasing fishing pressure.